2021
DOI: 10.4244/eij-d-21-00089
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary optical coherence tomography: state of the art and future directions

Abstract: Optical coherence tomography (OCT) has been increasingly utilised to guide percutaneous coronary intervention (PCI). Despite the diagnostic utility of OCT, facilitated by its high resolution, the impact of intracoronary OCT on clinical practice has thus far been limited. Difficulty in transitioning from intravascular ultrasound (IVUS), complex image interpretation, lack of a standardised algorithm for PCI guidance, and paucity of data from prospective clinical trials have contributed to the modest adoption. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 124 publications
(145 reference statements)
1
94
0
Order By: Relevance
“…Compared to IVUS, OCT has greater axial and spatial resolution that might be helpful in CAE to assess atherosclerotic plaque features, thrombus burden and mechanisms of PCI failure. However, its application in large vessel is limited by the low penetration depth, with loss of image definition as the distance of the anatomical structures from the lens increases (62).…”
Section: Clinical Presentation and Diagnostic Assessmentmentioning
confidence: 99%
“…Compared to IVUS, OCT has greater axial and spatial resolution that might be helpful in CAE to assess atherosclerotic plaque features, thrombus burden and mechanisms of PCI failure. However, its application in large vessel is limited by the low penetration depth, with loss of image definition as the distance of the anatomical structures from the lens increases (62).…”
Section: Clinical Presentation and Diagnostic Assessmentmentioning
confidence: 99%
“…It has been proved that an EEL-based strategy of stent sizing caused the minimal stent area to be similar to that in the case of IVUS-guided PCI. At the same time, a lower number of untreated post-PCI complications was observed [27].…”
Section: Predictors Of Stent Expansionmentioning
confidence: 85%
“…Another issue is that distal EEL diameter, even with the use of modern software, may be visualized via OCT among 85% of the cases by the particular catheterization laboratory. In 95% of cases, this can be conducted by the OCT core laboratory within 5 mm of the original angiographically selected segment for reference [27].…”
Section: Predictors Of Stent Expansionmentioning
confidence: 99%
“…Lastly, recent intravascular imaging studies indicate that calcified nodules are more likely found in the RCA, resulting in a higher risk of stent under expansion and more adverse events compared to calcified lesions without a calcified nodule 15,16 . Although optical coherence tomography and intravascular ultrasound imaging were not tracked in this analysis, previous studies have shown that imaging optimizes and improves PCI results regardless of lesion location and ethnicity 17,18 . However, we hypothesize that patients with RCA lesions, such as the HL patients in our retrospective analysis, may especially require intravascular imaging to better characterize the calcified lesions to properly plan for vessel preparation to obtain optimal results.…”
Section: Discussionmentioning
confidence: 96%